The role of proxy internet use in sequential pathways of digital exclusion: An empirical test of a conceptual model. (March 2022) - Petrovčič, Andraž; Reisdorf, Bianca C.; Prevodnik, Katja; Grošelj, Darja
Abstract: Proxy internet use has been identified as a viable strategy for achieving tangible internet outcomes and overcoming digital exclusion. In this study, we distinguish between proxy users who perform online activities for others and users-by-proxy, for whom activities are performed. We present a conceptual extension of the model of compound and sequential digital exclusion. We propose 18 hypotheses to understand how proxy use and use-by-proxy mediate the effects of internet skills on internet uses and outcomes. The model was tested using a path analysis based on data from a nationally representative sample of 535 internet users in Slovenia (males: 48.6%; age range: 18–84 years; M = 42.0 years). The results showed positive pathways between operational and creative skills, proxy use, internet uses, and outcomes. Internet users with high operational and creative skills, who were proxy users, expanded their online engagement and increased their tangible outcomes. Conversely, creative skills were negatively associated with use-by-proxy, which had no significant effects on internet uses and outcomes. Overall, our findings reveal a multidimensional aspect of indirect internet use and its importance in achieving digital equality, highlighting the importance of framing proxy internet use within established models of digital exclusion. Highlights: Proxy use and use-by-proxy were studied in a sequential model of digital inclusion. Operational and creative skills were positive predictors of proxy use. Proxy use had a positive effect on use-by-proxy, internet uses and outcomes. Creative skills were negatively associated with use-by-proxy among internet users. Use-by-proxy had a limited potential for fostering inclusive digital engagement.